2022
DOI: 10.3390/v14010096
|View full text |Cite
|
Sign up to set email alerts
|

Are There Still Difficult-to-Treat Patients with Chronic Hepatitis C in the Era of Direct-Acting Antivirals?

Abstract: Difficult-to-treat populations with chronic hepatitis C (CHC), in the era of interferon treatment, included patients with liver cirrhosis, kidney impairment, treatment-experienced individuals, and those coinfected with the human immunodeficiency virus. The current study aimed to determine whether, in the era of direct-acting antivirals (DAA), there are still patients that are difficult-to-treat. The study included all consecutive patients chronically infected with hepatitis C virus (HCV) who started interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…The study of Pabjan et al [45] also demonstrated that in addition to GT3-infected and cirrhotic patients, male sex and treatment experience significantly reduced the chances of virologic response. However, in our study, there was no significant difference in the SVR12 rate between males and females in both the ITT and PP populations.…”
Section: Discussionmentioning
confidence: 97%
“…The study of Pabjan et al [45] also demonstrated that in addition to GT3-infected and cirrhotic patients, male sex and treatment experience significantly reduced the chances of virologic response. However, in our study, there was no significant difference in the SVR12 rate between males and females in both the ITT and PP populations.…”
Section: Discussionmentioning
confidence: 97%
“…Liver cirrhosis was also a risk factor of reinfection in our study, with an incidence of 18.1/100PY noted (AHR, 3.94; 95% CI 1.09-14.22), though we could not distinguish reinfection from relapse due to a lack of phylogenetic analysis of HCV strains. Nonetheless, Pawel et al demonstrated significantly lower response rates in patients with liver cirrhosis in their research (odds ratio, 4.43; 95% CI, 1.59-12.38) [24].…”
Section: Discussionmentioning
confidence: 79%
“…The very high overall success rate of DAA therapy, exceeding 95%, has made the problem of nonresponse to treatment in chronic hepatitis C marginal. However, experience in recent years shows that there are still patients with a lower chance of therapeutic success [19][20][21]. Effective retreatment options for patients who have not responded to DAA therapy are a key prerequisite for achieving the WHO's goal of HCV elimination.…”
Section: Discussionmentioning
confidence: 99%